2016
DOI: 10.1038/srep38612
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protein structural elements responsible for the diversity of sequence preferences among Mini-III RNases

Abstract: Many known endoribonucleases select their substrates based on the presence of one or a few specific nucleotides at or near the cleavage site. In some cases, selectivity is also determined by the structural features of the substrate. We recently described the sequence-specific cleavage of double-stranded RNA by Mini-III RNase from Bacillus subtilis in vitro. Here, we characterized the sequence specificity of eight other members of the Mini-III RNase family from different bacterial species. High-throughput analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Consequently, the available data (in some cases including the crystal structure of the protein partner in the apo form) were used to guide macromolecular docking and modelling of RNA-protein interactions, providing functional insight that could not be obtained from structures of the components in isolation from each other. One example includes the BsMiniIII endonuclease, which crystallized only in the apo form but not in complex with its dsRNA substrate and for which an RNP complex structure was modelled [ 132 ] and used to guide the successful engineering of substrate preference [ 133 ]. For CMTr2 methyltransferase, we were unable to obtain sufficient amounts of protein for crystallization and had to model the structure of the complex with a 5′-capped RNA substrate to obtain insights into the mechanism of substrate recognition [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the available data (in some cases including the crystal structure of the protein partner in the apo form) were used to guide macromolecular docking and modelling of RNA-protein interactions, providing functional insight that could not be obtained from structures of the components in isolation from each other. One example includes the BsMiniIII endonuclease, which crystallized only in the apo form but not in complex with its dsRNA substrate and for which an RNP complex structure was modelled [ 132 ] and used to guide the successful engineering of substrate preference [ 133 ]. For CMTr2 methyltransferase, we were unable to obtain sufficient amounts of protein for crystallization and had to model the structure of the complex with a 5′-capped RNA substrate to obtain insights into the mechanism of substrate recognition [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that the small RNA peaks were not always produced at the 5′- or 3′-end, and this was mainly related to the nucleotide sequence components. Sequence cleavage preference had been shown in RNase III family proteins, different Dicer-like enzymes in Paramecium have different cleavage preference sites (Hoehener et al, 2018), and BsMiniIII in B. subtilis has a strong preference for ACCU/AGGU as a cleavage site (Glow et al, 2016). These results are consistent with our high-throughput sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Most results indicated that members of Coleopteran are more sensitive to RNAi than those of Lepidoptera insects (Terenius et al, 2011; Ivashuta et al, 2015; Joga et al, 2016). Thus, the difference in RNAi efficiencies between these two insect orders may result from a difference in their genomes’ nucleotide compositions, the codon bias of their genes (Behura and Severson, 2012), enzyme-substrate contacts (Glow et al, 2016), RNAi pathway-related gene (Dowling et al, 2016), or various environmental differences that result in differences in dsRNA stability (Spit et al, 2017). Here, we discovered that there was a large difference in the dsRNA’s cleavage between Lepidoptera and Coleoptera insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other RNase IIIs that contain a dsRNA-binding domain and separate catalytic domain(s), Mini-III RNase (mR3), which was first identified in Bacillus subtilis and participated in the maturation of 23s ribosomal RNA, contains a catalytic domain but lacks a recognizable dsRNA-binding domain ( Redko et al, 2008 ). It has been shown that mR3s from different bacterial species could cleave long dsRNA with a certain degree of sequence specificity ( Glow et al, 2016 , 2015 ). Interestingly, deletion of the α5β-α6 loop of B. subtilis mR3 results in loss of catalytic activity and preservation of sequence-independent dsRNA-binding activity ( Glow et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%